DEVELOPMENT OF BORDER RURAL AREAS IN UKRAINE BASED ON IMPLEMENTATION OF REGIONAL MARKETING MECHANISMS - Viktor Borshchevskiy; Iryna Kravtsiv; Vitaliy Krupin (Polityki Europejskie, Finanse i Marketing)
The article is devoted to understanding the role of marketing in the development of Ukrainian rural areas, which are neighbouring with countries of greater economic power – the EU member states. Such closeness to such neighbour is an opportunity and a threat at the same time, yet with proper preparations and properly implemented measures it could turn into bilateral benefit. Marketing of territories, agrarian marketing, diversification of rural economy, modern national and regional management approaches – that is what Ukrainian rural areas require in order to prepare them for closer integration with EU, for preserving and deepening of their development potential. In order to understand these issues the article elaborates them and the environment in which Ukrainian border rural areas are functioning. Based on this analysis the key priorities for diversification of the economy of border rural areas are offered, which would aid forming a complex system of support for the local rural communities in border regions of Ukraine.